Efektifkah Bahan Tayang Interaktif untuk Meningkatkan Pengetahuan Pubertas pada Siswa Sekolah Dasar? - Sri Handayani; Murfiah Dewi Wulandari (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2022)
Background: One of the stages of child development is puberty. Puberty is common at the age of a dozen years, usually children undergo a change towards adulthood. These changes can be physical, mental, and social changes. In the face of puberty requires sufficient knowledge. Method: The approach in this study was quantitative. The data obtained were processed used statistical analysis. The study design used one group pretest and posttest. Result: The results of the study obtained stated that the use of interactive PowerPoint can increase the average value of pretest-posttest by 2.87. The result of the hypothesis test based on the t-test was obtained that the result of . (-3,761 < -2,045) then Ho was rejected. There were differences in student learning outcomes in the pretest and posttest. That way there was an increase in knowledge on puberty material for grade 6 students of SD Muhammadiyah PK Kottabarat Implication: Based on the results obtained, there were several' suggestions related to this study: First for schools, the school should provide facilities in the form of facilities and infrastructure that can support learning. Second, for teachers, it is expected to be able to develop innovative learning media. Third, for other researchers, it is hoped that this study can provide benefits for conducting the next study. Novelty: This study revealed the effectiveness of using media to improve students' knowledge.